Research progress in the creep resistance of porous metal materials - LI Cong; XIAO Xinyue; CHEN Jian (Jixie qiangdu, 2025)
Porous metals are widely used in filtration, catalysis, adsorption and heat transfer because of their excellent mechanical properties. However, creep failure is a primary failure mode for porous metal parts experiencing the high temperature and constant stress. The research progress of the creep resistance of porous metal materials was summarized from four aspects, pore structure， edge structure, micro-defect and creep life prediction. The effects of pore structure, such as porosity, pore shape and pore diameter, on the stress index, creep resistance and deformation mechanism of porous metals were expounded. The creep resistance of the hollow and solid edge under different stress conditions was analyzed, and the effect law of edge size on the creep rate of porous metals was revealed. The effect of micro-defects on the creep mechanism of porous metals was clarified, and the constitutive model for predicting the creep life of porous metals was introduced. These studies provide scientific guidance for the long-life service and reliable operation of porous metal structures.